Human apolipoprotein E as a reservoir of cryptic bioactive peptides: The case of ApoE 133‐167. (14th June 2018) - Zanfardino, Anna; Bosso, Andrea; Gallo, Giovanni; Pistorio, Valeria; Di Napoli, Michela; Gaglione, Rosa; Dell'Olmo, Eliana; Varcamonti, Mario; Notomista, Eugenio; Arciello, Angela; Pizzo, Elio
Abstract : Bioactive peptides derived from the receptor‐binding region of human apolipoprotein E have previously been reported. All these peptides, encompassing fragments of this region or designed on the basis of short repeated cationic sequences identified in the same region, show toxic activities against a broad spectrum of bacteria and interesting immunomodulatory effects. However, the ability of these molecules to exert antibiofilm properties has not been described so far. In the present work, we report the characterization of a novel peptide, corresponding to residues 133 to 167 of human apolipoprotein E, here named ApoE (133‐167). This peptide, besides presenting interesting properties comparable with those reported for other ApoE‐derived peptides, such as a direct killing activity against a broad spectrum of bacteria or the ability to downregulate lipopolysaccharide‐induced cytokine release, is also endowed with significant antibiofilm properties. Indeed, the peptide is able to strongly affect the formation of the extracellular matrix and also the viability of encapsulated bacteria. Noteworthy, ApoE (133‐167) is not toxic toward human and murine cell lines and is able to assume ordered conformations in the presence of membrane mimicking agents. Taken together, collected evidences about biological and structural properties of ApoE (133‐167) open new perspectives in the design of therapeutic agents based on human‐derived bioactive peptides. Abstract : A new cryptic host defense peptide has been identified in human apolipoprotein E. ApoE 133‐167 exerts antibiofilm actions and broad spectrum antimicrobial activities. ApoE 133‐167 induces mitigation of proinflammatory mediators production in LPS‐induced macrophages.